Raising Awareness of Balanced Nutrition among Pregnant Women to Prevent Stunting in Rural Samarinda, East Kalimantan - Kurniati Dwi Utami; Yuni Sulistiawati; Wijianto; Ni Nyoman Murti; Mareyke Yolanda Lusia Sepang (Sustainable Applied Modification Evidence Community (SAMEC), 2025)
Stunting is a significant public health problem in Indonesia, including in East Kalimantan. Purpouse: This study aims to identify factors that influence pregnant women's nutrition awareness in rural Samarinda and develop effective strategies to improve nutrition education to prevent stunting. Methods: The study used a qualitative and quantitative approach (mixed-methods) to obtain a comprehensive picture of the level of awareness and understanding of balanced nutrition among pregnant women. Qualitative in-depth interviews and observations were used to understand the social, cultural, and economic factors that contribute to the nutritional consumption patterns of pregnant women in rural South Indonesia. Results: The results showed that most pregnant women had moderate (45%) and low (30%) levels of nutritional awareness. Education level (60%) and family support (65%) had the highest influence on pregnant women, at 60% and 65%, respectively. Conclusion: The findings of the study suggest that nutrition interventions should not only be conducted from an educational aspect but also take into account social and cultural aspects to be more effective in improving pregnant woman's nutritional awareness and preventing stunting, especially through more intensive and community-based education.